(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Through this article, it is now covered that the qualitative and effective conduct of teacher activities is the main pedagogical problem before them, along with the development of our society and the development of growing young people as a harmonious mature person with every completion, as well as the responsible work of pedagogical staff.